2020
DOI: 10.1038/s41467-020-18539-w
|View full text |Cite
|
Sign up to set email alerts
|

Authentic self-expression on social media is associated with greater subjective well-being

Abstract: Social media users face a tension between presenting themselves in an idealized or authentic way. Here, we explore how prioritizing one over the other impacts users’ well-being. We estimate the degree of self-idealized vs. authentic self-expression as the proximity between a user’s self-reported personality and the automated personality judgements made on the basis Facebook Likes and status updates. Analyzing data of 10,560 Facebook users, we find that individuals who are more authentic in their self-expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 58 publications
3
59
0
Order By: Relevance
“…For instance, Orehek and Human (2017) find platforms such as Twitter, can be an effective medium for not only accurate but also positive self-expression. Further, online authenticity of the self has been linked to indicators of subjective well-being (Reinecke and Trepte, 2014;Bailey et al, 2020). While indicators of well-being were not explicitly explored in this study, we did find that individuals regularly engaged in (de)emphasizing, hiding or selectively revealing gendered aspects.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…For instance, Orehek and Human (2017) find platforms such as Twitter, can be an effective medium for not only accurate but also positive self-expression. Further, online authenticity of the self has been linked to indicators of subjective well-being (Reinecke and Trepte, 2014;Bailey et al, 2020). While indicators of well-being were not explicitly explored in this study, we did find that individuals regularly engaged in (de)emphasizing, hiding or selectively revealing gendered aspects.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, past research on gender portrayals in popular media finds, "the search for a seemingly authentic life involves tensions" (Zayer et al, 2012, p. 349). Regarding social media specifically, Bailey et al (2020) highlight the tensions between authentic expression and self-idealization. A desire for authenticity while simultaneously experiencing the tensions brought about by closely monitoring social praise is expressed by our informant, Mo: "If you don't get this amount of likes, you're going to be destroyed.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-review 21 reported that, although the effect of digital media use on well-being was generally negative and small, when the type of usage involved active social interactions, it was positively related to well-being. Furthermore, a recent study 74 analyzed data from 10,560 Facebook users and reported that authentic self-expression (versus self-idealizing) posting behaviours on social media were related to higher life satisfaction. Similarly, Gonzales and colleagues 75 found that more meaningful text-based interactions through social media instant messaging applications were associated with higher self-esteem with respect to face-to-face or call-based communication; although, the effects were overall very small and lasted for few days.…”
Section: Discussionmentioning
confidence: 99%
“…This includes concerns over the number of likes and comments [31], the need for social comparison and jealousy of others' social media posts [32,33], and feeling dejected from negative comments [34]. Finally, as authentic selfexpression on social media is associated with greater subjective well-being [35], we sought to evaluate the potential role of vulnerable narcissism in portraying oneself differently on social media [36].…”
Section: Narcissism and Social Media Usementioning
confidence: 99%